2019
DOI: 10.5194/bg-2019-302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microtopography is a fundamental organizing structure in black ash wetlands

Abstract: <p><strong>Abstract.</strong> All wetland ecosystems are controlled by water table and soil saturation dynamics, so any local scale deviation in soil elevation represents variability in this primary control. Wetland microtopography is the structured variability in soil elevation, and is typically categorized into a binary classification of local high points (<q>hummocks</q>) and local low points (<q>hollows</q>). … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…In contrast, hummock-hollow terrain and patterns may be less evident at drier sites where soils are nearly always unsaturated and aerobic, weakening the elevation-productivity feedback (Miao et al, 2013;Miao et al, 2017). In a companion study we found support for this overall model, where we observed vegetation and soil chemistry associations with hummock structures, indicative of elevation-productivity feedbacks, and that these associations were greatest at the wettest sites (Diamond et al, 2019). Here, we add to that work by assessing the structure and pattern of hummock features and the extent to which they are influenced by the hydrologic regime.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…In contrast, hummock-hollow terrain and patterns may be less evident at drier sites where soils are nearly always unsaturated and aerobic, weakening the elevation-productivity feedback (Miao et al, 2013;Miao et al, 2017). In a companion study we found support for this overall model, where we observed vegetation and soil chemistry associations with hummock structures, indicative of elevation-productivity feedbacks, and that these associations were greatest at the wettest sites (Diamond et al, 2019). Here, we add to that work by assessing the structure and pattern of hummock features and the extent to which they are influenced by the hydrologic regime.…”
Section: Introductionmentioning
confidence: 54%
“…3). The three lowland sites were control plots from a long-term experimental randomized block design on black ash wetlands (blocks 1, 3, and 6; Slesak et al, 2014;Diamond et al, 2018). We considered hydrogeomorphic variability among sites an important criterion, as it allowed us to capture expected differences in hydrologic regime and, thus, differences in the strength of our predicted control on microtopographic generation (Fig.…”
Section: Site Descriptionsmentioning
confidence: 99%
See 3 more Smart Citations